Is frequency of family meals associated with parental encouragement of healthy eating among ethnically diverse eighth graders?. Issue 5 (7th May 2013) - Poulos, Natalie S; Pasch, Keryn E; Springer, Andrew E; Hoelscher, Deanna M; Kelder, Steven H
Abstract Objective The purpose of the present study was to explore the relationship between family meals and parental encouragement of healthy eating overall and by ethnicity. Design Family meal frequency was measured with one item asking how many times in the past 7 d all or most of the family ate a meal together, which was then categorized to represent three levels of family meals (≤2 times, 3–6 times and ≥7 times). Parental encouragement of healthy eating assessed how often parents encouraged the student to eat fruits and vegetables, drink water, eat wholegrain bread, eat breakfast and drink low-fat milk (never to always). An overall scale of parental encouragement of healthy eating was created. Mixed-effect regression analyses were run controlling for gender, ethnicity, age and socio-economic status. Moderation by ethnicity was explored. Setting Middle schools. Subjects Participants included 2895 US eighth grade students participating in the Central Texas CATCH (Coordinated Approach To Child Health) Middle School Project (mean age 13·9 years; 24·5 % White, 52·7 % Hispanic, 13·0 % African-American, 9·8 % Other; 51·6 % female). Results Eating more family meals was significantly associated with having parents who encouraged healthy eating behaviours (P for trend <0·001). The number of family meals was positively associated with encouragement of each of the healthy eating behaviours (P for trend <0·0001). There were no differences in the relationships by ethnicity of the students. Conclusions Families who eat together are more likely to encourage healthy eating in general. Interventions which promote family meals may include tips for parents to increase discussions about healthy eating.